Curricular Engagement with Reference to Vygotski’s Thoughts - Nagina S. Mali; Smt. Saraswati A. Kamble (Lingkar Studi Komunikasi (LISKI), 2020)
Education helps to learner’s personal, social and academic development. Society is the community that provides positive environment to school where learner learns. It is universal expectation from learner that they should become active and make interaction with society. Nowadays, students are becoming active, creative and collaborative. But how learner learns is a valuable dimension of learner’s social development. Where learner is unable to learn individually, in that case there is need of peers, adults and assisted media that can promote and help in learning joyfully. Vygotski's thoughts are related to learner’s social development. His ZPD (Zone of Proximal Development) is a valuable contribution in education. He considers learner’s language, culture, intellectual level, peers, media and adult affects on learner’s development. Curricular Engagement is one of the Teaching-Learning approach that involves in learner’s social development. It is interactions between school, learner, society, teacher and media. Interaction builds knowledge, creates healthy relationship, leads to win-win approach and provides cultural environment. The similarities of Vygotski’s theory and Curricular Engagement both are emphasizes on interaction with peer, teacher, media and adult. In this conceptual paper researchers have explained how Vygotskian thoughts support to curricular engagement with multicultural, multilingual context.